Prospecting of pathogen-derived elicitors for the control of tomato bacterial spot - Simões, Camila Tonelotti [UNESP]; Carvalho, Valdeir Nunes [UNESP]; de Almeida Halfeld-Vieira, Bernardo (Polish Academy of Sciences Chancellery, 2021)
Plants can recognize molecules derived from pathogens and trigger systemic acquired resistance (SAR). In phytopathogenic bacteria, elicitors are constituent components of cellular structures, such as flagellin. We sought to select structural components of Xanthomonas spp. incompatible with tomato, aiming to control bacterial spot (Xanthomonas perforans). Initially, cell suspensions from 11 Xanthomonas spp. isolates were infiltrated into the leaves to assess their ability to cause a hypersensitivity response (HR) and the incompatible ones had their flagellin purified. The flagellin of the isolates were first applied at different concentrations, via infiltration and spraying. The pathogen, X. perforans, was inoculated after 24 h, to assess whether there would be any harmful reaction. No harmful reaction was observed in any treatment. Then, a second experiment was conducted to assess the severity of all isolates, at a concentration of 8.35 μg · ml–1, via spraying, infiltration, and soil. The greatest reduction in Area Under the Disease Progress Curve (AUDPC) was observed in the treatment with XapRR, applied via spraying. Thus, prospecting for elicitors is the first step in developing a product for agricultural use. The flagellin elicitor of XapRR is promising and capable of producing these molecules on a large scale.
Keywords: Hypersensitivity response; Incompatibility; Phytopathogenic bacteria; Xanthomonas euvesicatoria pv. perforans